Використання технології 3D друку (CJP) для створення композитних трьохмірних виробів на основі вуглецевих наноструктур - Золотаренко , Ол.Д.; Золотаренко, Ан.Д.; Аханова, Н.Є.; Уалханова, M.; Щур, Д.В.; Габдуллін , M. T.; Мироненко, Т.В.; Золотаренко , О.Д.; Рудакова , О.П.; Чимбай , М.В.; Каменецька, О.А.; Гаврилюк, О.О.; et al. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2023)
The conditions for the use of carbon nanotubes (CNT) synthesized by the pyrolytic method are described and a method for their use in a CJP 3D printer is developed. Methods for preparing synthesis products for use in 3D printers of CJP, FDM, SLA, SLS technologies are described. In the research work, the fact was established and the advantages of the composite material (СNT - Al2O3) over the original ceramic material were listed. Also, the technique for creating composite 3D products from consumable mechanical mixtures (СNT/Al2O3) was considered, where the technology for their preparation was considered. The bending strength of 3D printed ceramics reinforced with carbon nanotubes has been measured. The resistance to mechanical fracture of composites obtained using helical and straight СNT has been studied, and it has been shown that when using helical СNT, the parts of the product do not crumble during destruction, but remain united even under load. A small review was made in the form of a table comparing the strength characteristics of various ceramics in comparison with the resulting composite (CNT - Al2O3). The strength parameters of the composite CNT - Al2O3 after its 3D printing and sintering were determined, with the content of CNT 0, 20, 30, 50% vol. A comparative analysis of the strength indicators for composite 3D products reinforced with spiral or straight CNT was carried out, where the content of CNT reached from 0 to 50% vol. All obtained materials (CNT, Al2O3 and a composite based on them) were studied by electron microscopy.